Spatial Distribution of Soil Organic Carbon under Agr9forestry and Traditional Cropping System in Hyper Arid Zone of Rajasthan - Soni, M L; Beniwal, R K; Yadava, N D; Talwar, H S (Annals of Arid Zone, 2016)
Short Communication